2018
DOI: 10.3390/en11113032
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of an Innovative Cascade Cycle Combining a Trilateral Cycle and an Organic Rankine Cycle (TLC-ORC) for Industry or Transport Application

Abstract: An innovative cascade cycle combining a trilateral cycle and an organic Rankine cycle (TLC-ORC) system is proposed in this paper. The proposed TLC-ORC system aims at obtaining better performance of temperature matching between working fluid and heat source, leading to better overall system performance than that of the conventional dual-loop ORC system. The proposed cascade cycle adopts TLC to replace the High-Temperature (HT) cycle of the conventional dual-loop ORC system. The comprehensive comparisons between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Wang et al [24] focused on comparison of subcritical ORC, dual-pressure (DORC) and transcritical ORC (TORC), adopting several different working fluids to recover low-grade energy. Yu et al [25] proposed a trilateral cycle combined with the organic Rankine cycle system to improve system performance.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [24] focused on comparison of subcritical ORC, dual-pressure (DORC) and transcritical ORC (TORC), adopting several different working fluids to recover low-grade energy. Yu et al [25] proposed a trilateral cycle combined with the organic Rankine cycle system to improve system performance.…”
Section: Introductionmentioning
confidence: 99%
“…The results revealed that the Trilateral Rankine cycle (TLC) can obtain a larger net output power than that of the ORC and Kalina systems. Yu et al [21] proposed an innovative cascade cycle combining a Trilateral Cycle and an ORC for industry or transport application to recover the exhaust thermal energy. Compared to the performance of a conventional dual-loop ORC system, the proposed novel cycle can improve the overall thermal efficiency and exergy efficiency by 33.7% and 31.2%, respectively [21].…”
Section: Introductionmentioning
confidence: 99%